1991
DOI: 10.1139/f91-245
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Stream Periphyton and Benthic Insects to Increases in Dissolved Inorganic Phosphorus in a Mesocosm

Abstract: Responses of stream periphytic algae and benthic insects to increases in dissolved inorganic phosphorus (P) were assessed in a streamside mesocosm. Controls and treatments were colonized continuously in summer by biota from the stream. P was maintained in the treatments at 10 μg∙L−1, [Formula: see text] times the concentration in the controls. In the treatments the biomass of chlorophyll a reached 3.5 times that of the controls, accompanied by an increase in Cyanophyta relative to diatoms. No difference was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
7
38
0
1
Order By: Relevance
“…Similarly, Hershey et al (1988) and Peterson et al (1993) showed that whole-stream N and P enrichment of the Kuparuk River in arctic Alaska dramatically altered food webs, consistently increasing secondary production of grazing insects and generally increasing standing stocks. Other mesocosm studies have reached the same conclusion-nutrient and resource limitation can be significant determinants of secondary production and standing stocks in many aquatic systems, (e.g., Mundie et al 1991, Perrin andRichardson 1997).…”
Section: Discussion Standing Stocks and Trophic Levelsmentioning
confidence: 66%
“…Similarly, Hershey et al (1988) and Peterson et al (1993) showed that whole-stream N and P enrichment of the Kuparuk River in arctic Alaska dramatically altered food webs, consistently increasing secondary production of grazing insects and generally increasing standing stocks. Other mesocosm studies have reached the same conclusion-nutrient and resource limitation can be significant determinants of secondary production and standing stocks in many aquatic systems, (e.g., Mundie et al 1991, Perrin andRichardson 1997).…”
Section: Discussion Standing Stocks and Trophic Levelsmentioning
confidence: 66%
“…Four conditions were additions of DIN (NO 3 --N + NH 4 +-N) to achieve a fully mixed concentration of 10 µg⋅L -1 , soluble reactive P (SRP) at 5 µg⋅L -1 , and the combination of N and P contrasted with a control having no nutrient additions. Although these nutrient doses were lower than those reported in other tests of nutrient deficiency in streams (Peterson et al 1983;Mundie et al 1991;Slaney et al 1994), they do exceed levels known to saturate both N-and P-limited growth of periphyton in rivers (Bothwell 1989(Bothwell , 1992. Each of the three treatments and the control were replicated four times producing a layout of 16 experimental units randomly assigned to treatments.…”
Section: Methodsmentioning
confidence: 62%
“…The concentration of added PO 4 -P that saturates Pdeficient growth can be <1 µg⋅L -1 (Bothwell 1989), but the concentration that saturates the accrual of areal biomass is higher due to diffusion effects within the algal mat (Bothwell 1989;Stevenson and Glover 1993). With the response by algae to nutrient augmentation in rivers, there can be an increase in benthic invertebrate abundance (Johnston et al 1990;Hart and Robinson 1990), largely due to feeding on the more abundant food supply in periphyton (Hershey et al 1988) which improves invertebrate survival (Mundie et al 1991). These additions of nutrients that limit algal growth will favour energy transfer based on autotrophy rather than heterotrophy (Peterson et al 1985) and can produce an increase in the biomass and yield of fish (Johnston et al 1990;Deegan and Peterson 1992) due to increased availability of the food organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid translation of increased autotrophic biomass into increased survival and emergence by sediment-dwelling chironomids has been previously documented for lakes (Welch et al 1988) and streams (Mundie et al 1991). Food level positively affected percent emergence, body size at emergence, and growth rate in laboratory-reared Chironomus tentans (Ball and Baker 1995).…”
Section: Benthic Invertebratesmentioning
confidence: 67%